Control of agitation rate and aeration for enhanced polygalacturonase production in submerged fermentation by Aspergillus sojae using agro‐industrial wastes. Issue 2 (16th May 2016) - Fratebianchi, Dante; Crespo, Juan Manuel; Tari, Canan; Cavalitto, Sebastian
Abstract: BACKGROUND: The koji mold Aspergillus sojae, an industrially important microorganism, can produce high levels of pectinases utilizing agro‐industrial wastes. This study introduces apricot and peach pomace, two agro‐industrial wastes barely considered as raw material for the generation of value‐added products, and focuses on its utilization together with orange peel for polygalacturonase production in submerged cultures using A. sojae . RESULTS: A Doehlert response surface methodology design conducted in shake flasks and applied individually with these three by‐products led to 60–80 U mL −1 polygalacturonase activity. In bioreactor studies performed with a mixture of apricot pomace and orange peel, by fixing stirrer speed to 600 rpm and cascading airflow to the dissolved oxygen tension up to 1.7 vvm, oxygen limitation problems were overcome and polygalacturonase activity values of 380 U mL −1 were achieved. CONCLUSION: A simple and efficient strategy to minimize oxygen limitation with the lowest possible shear stress is provided for stirred‐tank bioreactors working with highly viscous broths, so as to ultimately enhance microbial enzyme production. The polygalacturonase activity yields obtained in our study are among the highest reported in the literature. © 2016 Society of Chemical Industry